Sampan Leper Sebagai Adaptasi Ekologi Estuari Pada Masyarakat Kelurahan Pekan Arba, Kecamatan Tembilahan, Kabupaten Indragiri Hilir - Maulana T Y, Ahmad; Kahanna, Mutia; Septriani, Septriani (eScience Humanity Journal, 2024)
This research discusses "Sampan Leper as an Adaptation to Estuary Ecology in Pekan Arba Village Community, Tembilahan District, Indragiri Hilir Regency, Riau Province". The aim of this research is to describe the background to the creation of the leper canoe and its function in the lives of the people of Pekan Arba Village, Tembilahan District, Indragiri Hilir Regency, Riau Province. The theories used in this research are Julian Steward's ecological adaptation theory and Bronislaw Malinowski's functionalism theory. The method used is a qualitative method, with data collection techniques of observation, interviews, literature study and documentation. The results of this research show that leper canoes are a local means of transportation in the Pekan Arba community. Leper canoes were born from the adaptation made by the Pekan Arba people to an environment with an estuarine (tidal) character. The process of community adaptation in creating leper canoes went through several stages, namely, pucai canoes, pucai canoes combined with the shape of the cempakul fish, and until finally in 1985 the people of Pekan Arba succeeded in creating leper canoes. Leper canoes are the answer to all the problems experienced by the people of Pekan Arba regarding their environment and have several functions including ecological functions, economic functions, social functions and cultural functions.